Community Fish Refuge Profile for Sustainable Aquaculture and Community Fish Refuge- CFR component - Sean, Vichet; Ou, Phichong; Sun, Vathanak; chankrisna, chhiev (2024)
CFR profile combines the results of results at ground from 21 CFRs which are supported through the SAFR-CFR project.